ADAM8 expression in invasive breast cancer promotes tumor dissemination and metastasis - Mathilde Romagnoli; Nora D Mineva; Michael Polmear; Catharina Conrad; Srimathi Srinivasan; Delphine Loussouarn; Sophie Barillé‐Nion; Irene Georgakoudi; Áine Dagg; Enda W McDermott; Michael J Duffy; Patricia M. McGowan; et al. (EMBO Molecular Medicine, 2013)
Abstract The transmembrane metalloprotease‐disintegrin ADAM8 mediates cell adhesion and shedding of ligands, receptors and extracellular matrix components. Here, we report that ADAM8 is abundantly expressed in breast tumors and derived metastases compared to normal tissue, especially in triple‐negative breast cancers (TNBCs). Furthermore, high ADAM8 levels predicted poor patient outcome. Consistently, ADAM8 promoted an aggressive phenotype of TNBC cells in culture. In a mouse orthotopic model, tumors derived from TNBC cells with ADAM8 knockdown failed to grow beyond a palpable size and displayed poor vascularization. Circulating tumor cells and brain metastases were also significantly reduced. Mechanistically, ADAM8 stimulated both angiogenesis through release of VEGF‐A and transendothelial cell migration via β1‐integrin activation. In vivo, treatment with an anti‐ADAM8 antibody from the time of cell inoculation reduced primary tumor burden and metastases. Furthermore, antibody treatment of established tumors profoundly decreased metastases in a resection model. As a non‐essential protein under physiological conditions, ADAM8 represents a promising novel target for treatment of TNBCs, which currently lack targeted therapies and frequently progress with fatal dissemination.